Resin composition, resin molding, and method for imparting oil repellency to resin composition
A resin composition with cellulose nanofibers, silicone-coated zinc oxide, and wax addresses the challenges of oil repellency in plastics by creating a stable, UV-resistant surface with reduced adhesion and heat resistance.
Patent Information
- Application Number
- JP2024098951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
Existing methods for imparting oil repellency to plastics, such as coating or incorporating fatty acid amides, face issues like additional steps, cost, uneven dispersion leading to clouding, and health and environmental concerns from phenolic antioxidants.
A resin composition comprising cellulose nanofibers, silicone-coated zinc oxide, and wax is blended with a base resin to create a surface with unevenness, providing effective oil repellency.
The resin composition achieves stable oil repellency with reduced surface adhesion and resistance to UV degradation, eliminating the need for phenolic antioxidants and improving heat resistance.
Smart Images

Figure 2025000595000003 
Figure 2025000595000004 
Figure 2025000595000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a resin molded product, and a method for imparting oil repellency to a resin composition. [Background technology]
[0002] Plastics are used for various purposes, for example, as containers, because they are lightweight, easy to process, and do not rust like metals. In particular, in food containers, etc., problems such as cleaning due to residual oil, dripping due to poor oil drainage, and melting and perforation of the container due to partial high temperature during heating due to a large contact surface of the oil, are required to improve the oil repellency of plastic containers, etc. Up to now, methods known for improving the oil repellency of plastics include fluorine, silicone coating, and alumina deposition on the surface, and blending fatty acid amide into the resin to bleed it to bring out the oil repellency effect.
[0003] However, coating and deposition have issues such as time loss and cost issues due to the additional process. In addition, if fatty acid amide is poorly dispersed, it will bleed into the resin surface due to kneading, and will cause fatty acid aggregates, which will lead to cloudiness over time, a decrease in oil repellency, unevenness in the oil, and pinholes. In addition, when stored outdoors or under ultraviolet light sources such as fluorescent lights, the coating will deteriorate due to ultraviolet rays attacking the resin itself, making it necessary to add a phenolic antioxidant to the resin. It is said that phenolic antioxidants can have adverse effects on health if ingested over the long term, and there are concerns that they may cause water pollution and ecosystem effects in the environment. Furthermore, they can cause pinking (discoloration) due to radical reactions with other extender pigments (titanium oxide, calcium carbonate, etc.). Under these circumstances, there is a strong desire to develop a new method to impart oil repellency to plastics. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication 2010-184454 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a new method for imparting oil repellency to plastics. [Means for solving the problem]
[0006] Under such circumstances, the present inventors conducted extensive research and found that by blending cellulose nanofibers, silicone oil, silicone-coated zinc oxide, and wax in a resin composition containing a base resin, the cellulose nanofibers act as a dispersant for the silicone-coated zinc oxide and wax, and unevenness resulting from the silicone-coated zinc oxide is generated on the surface of a molded article obtained by curing the resin composition, thereby imparting oil repellency to the molded article. Accordingly, the present invention provides the following: Item 1. A resin composition comprising a base resin, cellulose nanofibers, silicone oil, silicone-coated zinc oxide and wax.
[0007] Item 2. The resin composition according to Item 1, wherein the silicone-coated zinc oxide has an average particle size of 5 to 900 nm.
[0008] Item 3. The resin composition according to item 1 or 2, for use as a masterbatch.
[0009] Item 4. The resin composition according to item 1 or 2 for forming a molded product.
[0010] Item 5. The resin composition according to any one of Items 1 to 4, wherein the cellulose nanofibers have a fiber diameter of 3 nm or more, more preferably 5 nm or more.
[0011] Item 6. The resin composition according to any one of Items 1 to 5, wherein the cellulose nanofibers have a fiber diameter of 10 nm or less, more preferably 7 nm or less.
[0012] Item 7. The resin composition according to any one of Items 1 to 6, wherein the cellulose nanofibers have a fiber length of 300 nm or more, more preferably 400 nm or more, and more preferably 500 nm or more.
[0013] Item 8. The resin composition according to any one of Items 1 to 7, wherein the cellulose nanofibers have a fiber length of 10 μm or less, more preferably 900 nm or less, and more preferably 700 nm or less.
[0014] Item 9. The resin composition according to any one of items 1 to 8, wherein the cellulose nanofiber has an aspect ratio of 30 or more, more preferably 40 or more, more preferably 43 or more, more preferably 50 or more, more preferably 57 or more, and more preferably 71 or more.
[0015] Item 10. The resin composition according to any one of items 1 to 9, wherein the aspect ratio of the cellulose nanofibers is 3333 or less, more preferably 2000 or less, more preferably 300 or less, more preferably 233 or less, more preferably 180 or less, and more preferably 140 or less.
[0016] Item 11. The resin composition according to any one of items 1 to 10, wherein the base resin is at least one selected from the group consisting of polyolefins (e.g., polyethylene, polypropylene, etc., preferably polypropylene, etc.), polystyrene, vinyl chloride, and polyesters (e.g., polyethylene terephthalate, etc.).
[0017] Item 12. The resin composition according to any one of Items 1 to 11, wherein the average particle size of the silicone-coated zinc oxide is 50 nm or more, more preferably 100 nm or more, and more preferably 200 nm or more.
[0018] Item 13. The resin composition according to any one of Items 1 to 12, wherein the average particle size of the silicone-coated zinc oxide is 800 nm or less, more preferably 500 nm or less, and more preferably 300 nm or less.
[0019] Item 14. The resin composition according to any one of items 1 to 13, wherein the cellulose nanofibers are carboxymethylated cellulose nanofibers.
[0020] Item 15. The resin composition according to any one of items 1 to 13, wherein the wax has a melting point of 120° C. or lower.
[0021] Item 16. The resin composition according to any one of items 1 to 13, wherein the wax has a melting point of 70° C. or higher.
[0022] Item 17. The wax is a vegetable wax (e.g., carnauba wax, soy wax, behenic acid wax, etc., preferably carnauba wax, etc.), a mineral wax (e.g., beeswax, etc.), preferably a vegetable wax. The resin composition according to any one of items 1 to 16.
[0023] Item 18. The resin composition according to any one of items 1 to 17, wherein the melting point of the base resin is 300 ° C. or less, more preferably 250 ° C. or less, more preferably 230 ° C. or less, more preferably 200 ° C. or less, and more preferably 190 ° C. or less.
[0024] Item 19. The resin composition according to any one of items 1 to 18, wherein the melting point of the base resin is 100 ° C. or more, more preferably 130 ° C. or more, more preferably 150 ° C. or more, more preferably 170 ° C. or more, and more preferably 180 ° C. or less.
[0025] Item 20. The resin composition according to any one of items 1 to 19, wherein the mass ratio of the base resin to the cellulose nanofibers is 100:5-60.
[0026] Item 21. The resin composition according to any one of Items 1 to 20, wherein the mass ratio of the cellulose nanofibers to the wax is 3-20:20-70, preferably 5-15:30-50.
[0027] Item 22. The resin composition according to any one of Items 1 to 21, wherein the mass ratio of the cellulose nanofibers to the silicone-coated zinc oxide is 3-20:3-20, preferably 5-15:5-15.
[0028] Item 23. The resin composition according to any one of Items 1 to 21, wherein a mass ratio of cellulose nanofibers to silicone oil is 3-20:0.1-5, preferably 5-15:0.5-3.
[0029] Item 24. A resin molded product obtained by molding the resin composition according to any one of items 1, 2, and 4 to 22.
[0030] Item 25. The resin molded product according to item 24, having irregularities of 0.5 μm to 1 μm.
[0031] Item 26. The resin molded article according to item 24 or 25, which is a food container.
[0032] Item 27. A method for imparting oil repellency to a resin composition, comprising adding cellulose nanofibers, silicone oil, silicone-coated zinc oxide and wax to a base resin.
[0033] Item 28. The method according to Item 27, wherein the silicone-coated zinc oxide has an average particle size of 5 to 900 nm.
[0034] Item 29. The method according to item 27 or 28, for use as a masterbatch.
[0035] Item 30. The method according to item 27 or 28 for forming a molded body.
[0036] Item 31. The method according to any one of Items 27 to 30, wherein the fiber diameter of the cellulose nanofibers is 3 nm or more, more preferably 5 nm or more.
[0037] Item 32. The method according to any one of Items 27 to 31, wherein the cellulose nanofibers have a fiber diameter of 10 nm or less, more preferably 7 nm or less.
[0038] Item 33. The method according to any one of Items 27 to 32, wherein the fiber length of the cellulose nanofibers is 300 nm or more, more preferably 400 nm or more, and more preferably 500 nm or more.
[0039] Item 34. The method according to any one of Items 27 to 33, wherein the fiber length of the cellulose nanofibers is 10 μm or less, more preferably 900 nm or less, more preferably 700 nm or less.
[0040] Item 35. The method according to any one of Items 27 to 34, wherein the cellulose nanofibers have an aspect ratio of 30 or more, more preferably 40 or more, more preferably 43 or more, more preferably 50 or more, more preferably 57 or more, and more preferably 71 or more.
[0041] Item 36. The method according to any one of Items 27 to 35, wherein the aspect ratio of the cellulose nanofibers is 3333 or less, more preferably 2000 or less, more preferably 300 or less, more preferably 233 or less, more preferably 180 or less, and more preferably 140 or less.
[0042] Item 37. The method according to any one of Items 27 to 36, wherein the base resin is at least one selected from the group consisting of polyolefins (e.g., polyethylene, polypropylene, etc., preferably polypropylene, etc.), polystyrene, vinyl chloride, and polyesters (e.g., polyethylene terephthalate, etc.).
[0043] Item 38. The method according to any one of Items 27 to 37, wherein the average particle size of the silicone-coated zinc oxide is 50 nm or more, more preferably 100 nm or more, more preferably 200 nm or more.
[0044] Item 39. The method according to any one of Items 27 to 38, wherein the average particle size of the silicone-coated zinc oxide is 800 nm or less, more preferably 500 nm or less, more preferably 300 nm or less.
[0045] Item 40. The method according to any one of Items 27 to 39, wherein the cellulose nanofibers are carboxymethylated cellulose nanofibers.
[0046] Item 41. The method according to any one of Items 27 to 40, wherein the wax has a melting point of 120° C. or lower.
[0047] Item 42. The method according to any one of items 27 to 41, wherein the wax has a melting point of 70° C. or higher.
[0048] Item 43. The method according to any one of Items 27 to 42, wherein the wax is a vegetable wax (e.g., carnauba wax, soy wax, behenic acid wax, etc., preferably carnauba wax, etc.), a mineral wax (e.g., beeswax, etc.), preferably a vegetable wax.
[0049] Item 44. The method according to any one of Items 27 to 43, wherein the melting point of the base resin is 300° C. or less, more preferably 250° C. or less, more preferably 230° C. or less, more preferably 200° C. or less, more preferably 190° C. or less.
[0050] Item 45. The method according to any one of items 27 to 44, wherein the melting point of the base resin is 100° C. or higher, more preferably 130° C. or higher, more preferably 150° C. or higher, more preferably 170° C. or higher, and more preferably 180° C. or lower.
[0051] Item 46. The method according to any one of Items 27 to 45, wherein the mass ratio of the base resin to the cellulose nanofibers is 100:5 to 60.
[0052] Item 47. The method according to any one of Items 27 to 46, wherein the mass ratio of cellulose nanofibers to wax is 3 to 20:20 to 70, preferably 5 to 15:30 to 50.
[0053] Item 48. The method according to any one of Items 27 to 47, wherein the mass ratio of the cellulose nanofibers to the silicone-coated zinc oxide is 3 to 20: 3 to 20, preferably 5 to 15: 5 to 15.
[0054] Item 49. The method according to any one of Items 27 to 548, wherein the mass ratio of cellulose nanofiber to silicone oil is 3 to 20: 0.1 to 5, preferably 5 to 15: 0.5 to 3. Effect of the Invention
[0055] According to the present invention, a new method for imparting oil repellency to plastics can be provided. [Brief description of the drawings]
[0056] [Figure 1] 4 shows the results of a comparative test of oil repellency contact angle (PP resin) in the examples. [Diagram 2] 4 shows the results of a comparative test of oil repellency contact angle (PS resin) in the examples. [Diagram 3] 4 shows the results of a comparative test of oil repellency contact angle (PE resin) in the examples. [Figure 4] 1 shows an outline of a tilt device in an embodiment. [Diagram 5] The results of tests on oil-repellency and stain resistance in the examples are shown below. [Figure 6] The results of tests on oil-repellency and stain resistance in the examples are shown below. [Figure 7] 4 shows the results of a heat resistance test (PP resin) based on the oil repellency effect in the examples. [Figure 8] 4 shows the results of a heat resistance test (PS resin) based on the oil repellency effect in the examples. [Figure 9] 4 shows the results of a heat resistance test (PP resin) based on the oil repellency effect in the examples. [Figure 10] 4 shows the results of surface observation in the examples. [Figure 11] 4 shows the results of observation of the surface side in the examples. [Figure 12] Schematic diagram of the filler dispersion state and the resin surface layer in one embodiment of the present invention. [Figure 13] 1 is a schematic cross-sectional view of a surface of a molded body according to an embodiment of the present invention, 1. A cured product of resin composition components other than zinc oxide, 2. Zinc oxide, 3. Bottom surface of a recess in the molded body, and h. Height of a protrusion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0057] resin composition The present invention provides a resin composition comprising a base resin, cellulose nanofibers, silicone oil, silicone coated zinc oxide and a wax.
[0058] The base resin is not particularly limited, and examples thereof include polyolefins (e.g., polyethylene, polypropylene, etc., preferably polypropylene, etc.), polystyrene, vinyl chloride, polyesters (e.g., polyethylene terephthalate, etc.), and polyolefin tow is preferred. These base resins can be used alone or in combination of two or more. The melting point of the base resin is, for example, 300°C or lower, preferably 250°C or lower, more preferably 230°C or lower, more preferably 200°C or lower, and more preferably 190°C or lower. The melting point of the base resin is, for example, 100°C or higher, preferably 130°C or higher, more preferably 150°C or higher, more preferably 170°C or higher, and more preferably 180°C or lower. In addition, the melting point of the base resin is preferably higher than the melting point of the wax. From the viewpoint of being able to prepare a composition while suppressing damage to the cellulose nanofibers by heat, it is preferable that the melting point of the base resin is in the above range.
[0059] The lower limit of the fiber diameter of the cellulose nanofiber is preferably 3 nm or more, more preferably 5 nm or more. The upper limit of the fiber diameter of the cellulose nanofiber is preferably 10 nm or less, more preferably 7 nm or less. The lower limit of the fiber length of the cellulose nanofiber is preferably 300 nm or more, more preferably 400 nm or more, more preferably 500 nm or more. The upper limit of the fiber length of the cellulose nanofiber is preferably 10 μm or less, more preferably 900 nm or less, more preferably 700 nm or less. The aspect ratio of the cellulose nanofiber is preferably 30 or more, more preferably 40 or more, more preferably 43 or more, more preferably 50 or more, more preferably 57 or more, more preferably 71 or more. The upper limit of the aspect ratio of the cellulose nanofiber is preferably 3333 or less, more preferably 2000 or less, more preferably 300 or less, more preferably 233 or less, more preferably 180 or less, more preferably 140 or less. The above fiber diameter, fiber length, and aspect ratio refer to the average values of the cellulose nanofiber contained in the resin composition. From the viewpoint of dispersibility of the silicone-coated zinc oxide, the size of the cellulose nanofiber is preferably within the above range. Also, it is preferable that the cellulose nanofiber is a carboxymethylated cellulose nanofiber.
[0060] As the silicone oil, dimethyl silicone oil is preferable. In addition, as the silicone oil, the dynamic viscosity coefficient ν (=μ / ρ, μ: viscosity coefficient, ρ: density) is 100 to 20000 mm 2 / S is preferable, and 200 to 15,000 mm 2 The dynamic viscosity coefficient can be measured in accordance with JIS-K-2283 (2000).
[0061] The average particle size of the silicone-coated zinc oxide is, for example, 5 nm or more, preferably 50 nm or more, more preferably 100 nm or more, more preferably 200 nm or more. The upper limit of the average particle size of the silicone-coated zinc oxide is, for example, 900 nm or less, preferably 800 nm or less, more preferably 500 nm or less, more preferably 300 nm or less. The silicone-coated zinc oxide is typically generally approximately spherical. In the present invention, the average particle size of the particles can be measured by a frequency spectrum analysis method using 180° backscattered light detection. As a measuring instrument, for example, a nanoparticle size measuring instrument NANOTRAC WAVE II manufactured by Nikkiso can be used. By silicone-treating zinc oxide having an uneven surface, a silicone layer having hydrophilicity is formed on the surface, and the unevenness of the surface acts synergistically to reduce the contact angle of liquids and solids, thereby improving water repellency and oil repellency.
[0062] The melting point of the wax is, for example, 120°C or less, preferably 90°C or less. The melting point of the wax is, for example, 70°C or more, preferably 80°C or more. From the viewpoint of high wettability to the filler, the melting point of the wax is preferably within the above range. Examples of the wax include vegetable waxes (e.g., carnauba wax, soy wax, behenic acid wax, etc., preferably carnauba wax, etc.), mineral waxes (e.g., beeswax, etc.), etc., and vegetable waxes are preferred. These waxes can be used alone or in combination of two or more.
[0063] In the present invention, the blending ratio of each component is not limited, but can be, for example, within the following ranges. The mass ratio of the base resin to the cellulose nanofibers ([mass of base resin]:[mass of cellulose nanofibers]) is, for example, 1000:1 to 100:25, preferably 1000:1 to 100:60, more preferably 100:1 to 100:30, more preferably 100:1 to 100:25, and more preferably 100:1 to 100:20. From the viewpoints of improving the diffusibility of the cellulose nanofibers and preventing the resin from becoming brittle, it is preferable that the mass ratio of the base resin to the cellulose nanofibers is within the above range.
[0064] The mass ratio of wax to cellulose nanofibers ([mass of wax]:[mass of cellulose nanofibers]) is, for example, 100:5 to 100:50, preferably 100:10 to 100:40, and more preferably 100:20 to 100:30. From the viewpoint of compatibility of the cellulose nanofibers with the wax, it is preferable that the mass ratio of wax to cellulose nanofibers is within the above range.
[0065] The mass ratio of the cellulose nanofibers to the silicone-coated zinc oxide ([mass of cellulose nanofibers]:[mass of silicone-coated zinc oxide]) is, for example, 100:15 to 100:667, preferably 100:33 to 100:300. From the viewpoint of suppressing CNF spotting and suppressing aggregation of excess zinc silicone in the resin, it is preferable that the mass ratio of the cellulose nanofibers to the silicone-coated zinc oxide is in the above range.
[0066] The mass ratio of the cellulose nanofibers to the silicone oil ([mass of the cellulose nanofibers]:[mass of the silicone oil]) is, for example, 1000:5 to 1000:1666, preferably 100:3 to 100:60. From the viewpoint of diffusibility in the resin, it is preferable that the mass ratio of the cellulose nanofibers to the silicone oil is in the above range.
[0067] In the present invention, it is preferable to further add a fatty acid amide (fatty acid amide) to the resin composition. Examples of the fatty acid amide include amide compounds having a structure in which a carboxyl group of a saturated or unsaturated fatty acid and ammonia are dehydrated and condensed. In this embodiment, examples of the fatty acid include those having 16 to 24 carbon atoms, preferably 18 to 22 carbon atoms, and linear fatty acids are preferred. Examples of the fatty acid amide include those represented by the formula RCONH2 (R is a fatty acid residue). Examples of the fatty acid amide include erucic acid amide, oleic acid amide, stearic acid amide, linoleic acid amide, palmitic acid amide, behenic acid amide, and the like. These fatty acid amides can be used alone or in combination of two or more. In this embodiment, the mass ratio of the fatty acid amide to the cellulose nanofibers ([mass of fatty acid amide]:[mass of cellulose nanofibers]) is, for example, 100:80 to 100:130, preferably 100:90 to 100:120, and more preferably 100:95 to 100:105. From the viewpoints of preventing slippage in the processing machine, preventing stickiness due to bleeding of the finished master batch, and preventing re-aggregation of the cellulose nanofibers when processed with a compound, it is preferable that the mass ratio of cellulose nanofibers to fatty acid amide is within the above range.
[0068] In an embodiment in which a fatty acid amide is used, the silicone-coated zinc oxide and the fatty acid amide are bonded to each other through the cellulose nanofiber as a conduit to form a complex, and the complex is dispersed in the resin composition. More specifically, for example, cellulose nanofiber: (CH 10 O5) n reacts with the fatty acid amide RCONH2 as follows: Reaction formula: (CH 10 O5) n -OH + RCONH2 → (CH 10 O5) n -O-RCONH2+ H2O The hydroxyl group (OH group) of the cellulose nanofiber reacts with the amide group (CONH2 group) of the fatty acid amide, and the cellulose nanofiber and fatty acid amide are linked by ester bonds, resulting in a compound in which the fatty acid amide functional group is bonded to the cellulose nanofiber. This is preferable because the silicone zinc oxide and fatty acid amide cellulose nanofibers are chemically bonded to each other with their respective coating materials, and the cellulose nanofibers physically intervene between the zinc oxide particles, allowing the particles to be firmly and three-dimensionally maintained in an evenly dispersed state. In an embodiment using a fatty acid amide, in order to mix a composite containing silicone-coated zinc oxide and fatty acid amide-coated cellulose nanofibers into a dissolved resin, it is important that the composite quickly diffuses into the oil without agglomeration. For this purpose, a capsule-like material that encapsulates the composite filler and easily diffuses into the base resin of the master batch is useful. From this perspective, the wax described above in the present invention is preferably a so-called carboxylic acid amide wax that has an amide structure and contains a carboxylic acid derivative. Examples of carboxylic acid amide waxes include carnauba wax, beeswax, microcrystalline wax, cattanite petroleum wax, and ozokerite wax. From the viewpoint of diffusion in oil, it is preferable that the melting point of the wax is lower than that of the fatty acid amide and the base resin.
[0069] In addition to the above-mentioned components, the resin composition of the present invention may optionally contain extender pigments (calcium carbonate, talc, kaolin, clay pigments, zeolite, diatomaceous earth, etc.), transparent nucleating agents, elastomers, UV antioxidants, heat stabilizers, mildew inhibitors, antibacterial agents, colorants, lubricants, etc.
[0070] The resin composition of the present invention includes a resin for master batches, and a resin composition for forming a molded body in which the resin for master batches is further mixed with a base resin, etc. In the present invention, the master batch refers to a compounding agent that is mixed in advance at a higher concentration than the final formulation in the process of mixing the compounding agent with the base resin. When a fine particle material such as zinc oxide is mixed with a resin such as a thermoplastic plastic, if it is added directly to the base resin, the fine particle material is likely to aggregate in the molten resin due to strong intermolecular attraction. Therefore, it is preferable to use a master batch based on a base resin in which a fine particle material is dispersed, since this can prevent poor dispersion during molding. When the base resin is melted, it is preferable that the master batch also dissolves and diffuses quickly at the same temperature. In addition, it is preferable to take measures to prevent the composite fine particle material contained in the dispersed master batch from recondensing. The appearance is required to be easy to work with and not to scatter, so a pellet shape (for example, a cylinder with 3 mmφ L = 5 mm) is desirable. In addition, it is desirable that the material is solid and not sticky at 90°C or less so that adhesion to a processing machine and blocking during storage do not occur.
[0071] In the masterbatch resin composition of the present invention, the mass ratio of the base resin to the cellulose nanofibers ([mass of base resin]:[mass of cellulose nanofibers]) is, for example, 100:5 to 100:30, preferably 100:10 to 100:25, and more preferably 100:15 to 100:20. In a resin composition for forming a molded body in which the masterbatch resin is further blended with a base resin or the like, the mass ratio of the base resin to the cellulose nanofibers ([mass of base resin]:[mass of cellulose nanofibers]) is, for example, 1000:1 to 100:10, and preferably 100:1 to 100:5.
[0072] The resin composition of the present invention can be produced by mixing each of the above components with a base resin. The order in which each component is mixed is not particularly limited. In one embodiment, for example, a mixture (or a composite) can be obtained by first mixing raw materials containing cellulose nanofibers, silicone oil, and silicone-coated zinc oxide, and optionally fatty acid amide. In this embodiment, a filler wax semi-finished product can be prepared by next mixing the mixture (or composite) with a raw material containing wax. Furthermore, a masterbatch resin composition can be obtained by mixing the filler wax semi-finished product with a raw material containing a base resin. Furthermore, a base resin and the like can be mixed to obtain a resin composition for forming a molded body.
[0073] A resin molded body can be obtained by molding the resin composition of the present invention. The molding method is not particularly limited, and examples thereof include extrusion molding, stretch molding, pressure injection molding, inflation (blowing molding), and forged composite molding (filling molding). According to the present invention, the resin molded body has unevenness on the surface caused by the silicone-coated zinc oxide, which is disposed near the surface of the resin molded body. The unevenness provides oil repellency to the resin molded body. It is preferable that the resin molded body has unevenness of 0.5 μm to 1 μm on the surface. In the present invention, the dimension of the unevenness on the surface of the resin molded body (height of the convex part) means the distance from the smooth part of the resin surface (a virtual plane including the plane forming the bottom surface of the concave part) to the apex of the convex part. Specifically, the height of the convex part means h in FIG. 13. Typically, the height of the convex portion can be calculated by taking images of the cross section in a certain range (for example, multiple locations (for example, 5 locations, etc.), measuring the height of the convex portion present within an appropriate length (for example, 30 μm) of each cross section, and calculating the average value. The unevenness can be calculated by analyzing images of the cross section of the resin molded body taken using a scanning electron microscope (SEM) using image analysis software (for example, PrecisionSEM3500 TOP Lens The oil repellent contact angle can be derived by observing the cross section of the molded product using a 3D scanning electron microscope (3D mode). Specifically, an image can be precipitated from the accelerating voltage and the reflection and scattering of the electron beam, and can be quantified using spherical nanosilica (diameter 100 nm) as a size standard. The resin molded product of the present invention preferably has an oil repellent contact angle of 70° or more. The oil repellent contact angle can be measured by the method described in the Examples below. The resin molded product of the present invention can take various forms, such as a sheet-like form and a form obtained by folding or stretching a sheet-like form. The resin molded product of the present invention may be a single sheet or a laminate of multiple sheets (for example, 2 to 5 sheets, 2 to 4 sheets, 2 to 3 sheets, etc.). In the case of a sheet-like form, the thickness can be set in the range of, for example, 80 to 120 μm, preferably 50 to 70 μm, and more preferably 20 to 40 μm.
[0074] By using the resin composition of the present invention, a resin molded body having an uneven surface can be obtained. The uneven surface reduces the adhesion rate of oil to the surface layer, resulting in an oil-repellent effect. Therefore, even if oil adheres to the molded body and is heated while in contact with the molded body, and the oil reaches a high temperature, the adhesion rate of the oil to the surface layer is low, so that the resin surface is prevented from melting and causing pinholes. In addition, since the uneven surface is formed by silicone-coated zinc oxide, deterioration due to ultraviolet rays and the like is reduced, and therefore long-term storage under fluorescent light sources in outdoors, warehouses, etc. is possible without using a phenol-based antioxidant.
[0075] The resin composition and resin molded article of the present invention can be used in various fields, for example, food containers, kitchenware (cooking utensils), automobile parts (oil tank covers, etc.), oil bottle containers (caps, bodies), oil-resistant gloves, oil-resistant covers, food packaging paper (oil-bleed prevention film), etc.
[0076] Method for imparting oil repellency to a resin composition As described above, according to the present invention, oil repellency is imparted to the resin composition obtained by blending cellulose nanofibers, silicone oil, silicone-coated zinc oxide, and wax into the base resin. Therefore, the present invention provides a method for imparting oil repellency to a resin composition, which includes a step of adding cellulose nanofibers, silicone oil, silicone-coated zinc oxide, and wax to the base resin. In this embodiment, the type and blending amount of each component, the blending method of each component into the base resin, etc. are the same as those described above.
[0077] Specific embodiments of the present invention will be described in more detail below using examples, but the present invention is not limited to the following examples. EXAMPLES
[0078] Manufacturing Example 1 The following (1) composite (composite filler), (2) filler wax semi-finished product, and (3) masterbatch semi-finished product were prepared in sequence: (1) Composites (composite fillers) Siliconized Zinc Oxide 47% Silicone 3% Fatty acid amides 25% -25% cellulose nanofiber (2) Filler wax semi-finished products The ratio of the composite material in (1) above to the wax that encases the composite material ·Composite 50% Carboxylic acid amide wax 50% (3) Semi-finished master batch products Polypropylene (PP) resin 40% Filler wax semi-finished products 60% The composition and content of the masterbatch semi-finished products are shown in Table 1.
[0079] [Table 1]
[0080] Manufacturing Example 2 Manufacturing method of semi-finished products containing oil-generating masterbatch fillers Pre-processing 1. Preparation of composite 2.5 kg of fatty acid amide is put into a rotating mixer (Henschel Mixer manufactured by Nippon Coke, Super Mixer manufactured by Kawata Manufacturing, Speed Mixer manufactured by Nippon Coke or EarthTechnica, etc.) and liquefied by heating to 130°C using an oil temperature regulator. 2.5 kg of cellulose nanofiber, 0.3 kg of silicone, and 4.7 kg of silicone-treated zinc oxide are added and mixed at 1500 rpm for 10 minutes. If the raw material rotates in a doughnut shape toward the center of the mixer at this time, the cellulose nanofiber fibers will curl up into a fluffy ball. For this reason, it is necessary to increase the rotation speed all at once and create a rotating shape of the raw material that rotates along with the mixer tank wall. After 10 minutes, stop mixing and start cooling the mixer to below 70℃. Mix at 300 rpm to form fine granules. The compound yield is 5.0 kg.
[0081] Pre-processing 2. Preparation of filler wax semi-finished products 5.0 kg of the composite obtained in pretreatment 1 and 5.0 kg of carboxylic acid derivative amide wax are added to a rotating mixer (Henschel mixer manufactured by Nippon Coke, Super mixer manufactured by Kawata Seisakusho, Speed mixer manufactured by Nippon Coke or Earth Technica, etc.) and mixed at 500 rpm at room temperature of 90°C for 5 minutes. The raw materials become a paste. The temperature is lowered once and the mixture is mixed again to make a powder, and 10 kg of semi-finished products are produced.
[0082] Pretreatment 3. Finishing of the dispersion of filler wax semi-finished products The powder mixture obtained in pretreatment 2 above is passed twice through a three-roll mill (Inoue Seisakusho, Imex Co., Ltd.) heated to 70° C. The mixture is discharged in flake form with a film thickness of 50 to 15 μm, and the clamping clearance of the rolls is appropriately adjusted according to the film thickness.
[0083] Pelletizing method for oil repellent masterbatch The filler wax semi-finished product obtained in the pretreatment 3 was pelletized and finished as an oil-repellent master batch. The blending example is shown in Table 2.
[0084] [Table 2]
[0085] As mentioned above, zinc oxide was used as a heat stabilizer during extruder processing. Also, elastomer was added to improve the toughness, cold resistance, and heat resistance of the resin.
[0086] The processing machine and processing conditions used for pelletization are as follows: processing machine Pelletizing Extruder Shibaura Machine Twin Screw Extruder TEM41 Processing conditions Cylinder Temperature Melting zone from inlet 185℃ Torque shear kneading zone 200℃ Discharge zone 190℃ Extruder 1 pass After cooling the strand in the water tank, it is cut into pellet size by the pelletizer. Drying at 50℃ using an Isuzu dryer Classification using a Dalton vibrating sieve Except for using PS resin or PE resin (LLDPE) instead of PP resin (homo, MFR=5), pellets based on PS resin or PE resin (LLDPE) were produced in the same manner as the PP resin-based pellets produced above. In this way, pellets of a total of three types of resin were produced.
[0087] Product molding using oil-repellent master batches In order to commercialize the oil-generating masterbatch prepared in Production Example 2 above, the user mixed the masterbatch into the base resin, and added 10 parts by mass of the masterbatch to 100 parts by mass of the base resin (PP resin) in the resin compound.
[0088] Oil repellent product molding Thin films ranging from 15μm to 200μm were produced from the compound by blown film molding.
[0089] Oil repellency test Test 1 Comparison of oil repellency contact angles We measured the contact angle between the film and oil to see if it had oil repellency, taking into consideration plastic containers for storing oil and films that come into contact with oil, and confirmed the difference.
[0090] Test conditions and equipment film Using the master batches based on PP resin, PS resin, or PE resin prepared by the above method or blank master batches described below, various films were formed using the "film preparation" process described below. 1.2 g of oil was dropped onto the films, and the contact angle was measured. Resin type Three types: PP resin (homo, MFR=5), PS resin and PE resin (LLDPE) ·Blank masterbatch Resin 90%, modifier elastomer 5%, processing heat stabilizer zinc stearate 5% Comparison test piece 100% of the blank master batch above is used Film production Processing machine: Inoue Seisakusho 8-inch hot mixing two-roll mixer, kneaded at 190℃ Film size: 120mm x 120mm, thickness: 70μm ·Oils and fats Salad oil Test results The results are shown in Figures 1 to 3. In each figure, the left side shows a blank, and the right side shows a film with 10 parts of the masterbatch added.
[0091] Fig. 1 PP resin, Fig. 2 PS resin, Fig. 3 PE resin As shown in Figures 1 to 3, the oil repellent contact angle was larger for the masterbatch-added film than for each of the above resins and blank products, confirming the oil repellent effect. The difference between a film with 5 parts of masterbatch added and a film with 10 parts added was tested for each resin, but the difference was only within ±3°, and no significant difference was confirmed. When an object is dropped onto a stationary flat surface and in contact with it, it seems that the number of parts added does not have an advantage in terms of oil repellency.
[0092] Test 2: Oil repellency and stain resistance We looked at plastic containers for storing oil and films that come into contact with oil, and checked the flow of oil by setting the angle of inclination to see if increasing the oil repellency would also improve oil drainage and stain resistance.
[0093] Test procedure Following the comparison of oil repellency contact angles in Test 1, the film was placed on a 45° inclined plate with salad oil dripped onto it and left for 10 seconds in a room at room temperature (25°C). The film dripping speed, oil residue on the surface, and oil streaks were checked.
[0094] Test conditions and equipment ·film Blank: 85% resin, 10% modifier elastomer, 5% heat stabilizer zinc stearate Comparison test piece: 10 parts of oil-repellent masterbatch added to 100 blank pieces Film Creation Processing machine: Inoue Seisakusho 8-inch hot mixing two-roll mixer, kneaded at 190℃ Film size: 120mm x 120mm, thickness: 70μm ·Oils and fats Salad oil ·Tilt device A schematic diagram of the tilt device is shown in Figure 4.
[0095] Test results The results are shown in Figure 5. The left side of the image is the blank, and the right side is the film with 10 parts of masterbatch added. Fig. 5 Left: PP film Fig. 5 Center: PS film Fig. 5 Right: PE film As shown in Figure 5, the blank product had not been completely cleaned of oil, and many residues remained, as well as thick streaks. The masterbatch-added film had an oil-repellent surface, so it cut well and left little residue. In addition, Figure 6 shows a comparison of the number of parts of masterbatch added to a PP resin film, with the film to which 10 parts were added having less residue and thinner streaks than the film to which 5 parts were added (Figure 6: 5 parts on the left and 10 parts on the right).
[0096] Test 3: Heat resistance due to oil repellency We checked whether heat resistance could be imparted by increasing oil repellency, with a view to applications such as PP and PS food containers that can be heated and recycled, and protective films for piping that are subject to high-temperature oil mist, etc.
[0097] Test procedure The film was placed on a paper container, and 3g of margarine was placed in the center of the film as an oil that heats up to around 300℃ when heated in a microwave. The paper container was heated for 30 seconds at 600W microwave output, and after stopping, it was removed and the state of the film was confirmed. Only the PP and PS films created in the measurement of oil repellency contact angle in Test 1 were used as test specimen films.
[0098] Test conditions and equipment ·film Blank: 85% resin, 10% modifier elastomer, 5% heat stabilizer zinc stearate Comparison test piece: 10 parts of oil-repellent masterbatch added to 100 blank pieces Film Creation Processing machine: Inoue Seisakusho 8-inch hot mixing two-roll mixer, kneaded at 190℃ Film size: 120mm x 120mm, thickness: 70μm ·Paper plate Size: Diameter 180mm, Height 8mm Material: Pulp Microwave safe ·Oils and fats Margarine lipids 72% ·microwave oven Panasonic NE-FL100 Output 600W 30 seconds set Test results The results are shown in Figures 7 to 9. As shown in Figures 7 and 8, pinholes occurred in the blank product, and the surface was beginning to melt due to the high-temperature oil. The film with added masterbatch did not have pinholes, and there was little melting on the surface. Also, the left and right sides of Figure 9 show a comparison of the amount of masterbatch added to a PP resin film, with the film with 10 parts added having a better film surface than the film with 5 parts added.
[0099] Test-4 Resin samples a to c in the lower row were prepared in the same manner as in the above-mentioned production examples, except that PP resin, elastomer, silicone-treated zinc oxide, fatty acid amide and / or master batch having the composition shown in Table 1 were used in the following mass ratios. a. 80% PP resin: 20% elastomer. b. 80% PP resin: 18% elastomer: 1.5% silicone-treated zinc oxide: 0.5% fatty acid amide. c. 80% PP resin: 11% elastomer: 9% oil repellent masterbatch in PP matrix. The resin sample was melted on a two-roll thermal mixing machine heated to 190°C, and a 70μm film was taken and observed under a microscope. Processing machine: Inoue Seisakusho 8-inch heat mixing roll Photographed with Keyence VHX-8000 at 2500x magnification The results of the surface observation are shown in FIG. Figure 10 Left: PP resin blank Figure 10 (center) Example of silicone-treated zinc oxide dispersed in 1.5% PP resin Figure 10 Right: An example of adding 10 parts of the inventive oil-repellent masterbatch to PP resin. The results of observation of the surface side (surface side of c) are shown in FIG. In a and b, the unevenness is not clearly visible. In c, the unevenness is visible.
[0100] The unevenness of the surface side of c (the unevenness at the top of the image is the surface) summary In order to increase the oil repellency of films, sheets, and molded products of thermoplastics, instead of coating, a master batch in which a filler that acts as an oil repellent is evenly dispersed is added during molding, which solves the problems of adding processes and costs. As described above, in this embodiment, the problem is solved by creating an uneven coating film on the surface of a molded product that has a permanent and stable oil repellency, rather than a discontinuous bleeding effect, by evenly dispersing the filler that has oil repellency in the master batch.
[0101] A filler made of zinc oxide particles with irregular uneven shape coated with silicone is placed between the fillers using cellulose nanofibers as a steric hindrance, maintaining the distance between the fillers, and further wetting the cellulose nanofibers with fatty acid amides makes it possible to achieve a consistent and stable bleeding effect on the surface without unevenness. Zinc oxide treated with silicone on the surface of a resin processed product creates zinc oxide unevenness of 0.5μm to 1μm on the resin surface, and cellulose nanofibers moistened with fatty acid amides promote the pushing up effect of zinc oxide particles to the surface, maintaining a dispersion network. When oil comes into contact with the resin, the oil floats up in dots on the resin surface (lotus leaf effect). As a result, the adhesion rate of oil to the surface is low, creating an oil-repellent effect, and when the oil adheres to and is heated while in contact with the molded product, it becomes hot and melts the resin surface, preventing pinholes and the like. Furthermore, zinc oxide and silicone, which are resistant to ultraviolet light attack, are dispersed in the filler, preventing resin deterioration. This makes it possible to store the product for long periods of time without deterioration, even outdoors or under fluorescent light sources in a warehouse, without the need for phenolic antioxidants.
[0102] FIG. 12 shows a schematic diagram of the filler dispersion state and the resin surface layer in this embodiment.
Claims
1. A resin composition comprising a base resin, cellulose nanofibers, silicone oil, silicone coated zinc oxide and a wax.
2. 2. The resin composition according to claim 1, wherein the silicone-coated zinc oxide has an average particle size of 5 to 900 nm.
3. The resin composition according to claim 1 for use as a masterbatch.
4. The resin composition according to claim 1 for forming a molded product.
5. The resin composition according to claim 1, wherein the cellulose nanofiber has an aspect ratio of 30 to 3333.
6. A resin molded product obtained by molding the resin composition according to any one of claims 1 to 5.
7. The resin molded product according to claim 6, having irregularities of 0.5 μm to 1 μm.
8. The resin molded article according to claim 6, which is a food container.
9. A method for imparting oil repellency to a resin composition comprising the steps of adding cellulose nanofibers, silicone oil, silicone coated zinc oxide and wax to a base resin.
10. The method of claim 9, wherein the silicone coated zinc oxide has an average particle size of 5 to 900 nm.
Citation Information
Patent Citations
Capping material
JP2010184454A